MicroRNA‐150 serves as a diagnostic biomarker and is involved in the inflammatory pathogenesis of Parkinson's disease. Issue 4 (20th February 2020) - Li, Haiting; Yu, Ling; Li, Min; Chen, Xiaohui; Tian, Qun; Jiang, Yanyan; Li, Nan
Abstract: Background: Dysregulation of microRNAs (miRNAs) has been reported to be involved in the neuroinflammatory pathogenesis of PD. This study aimed to investigate the serum expression of microRNA‐150 (miR‐150) in Parkinson's disease (PD) patients and further uncover the regulatory effect of miR‐150 on neuroinflammation. Methods: Quantitative Real‐Time PCR was used to measure the expression of miR‐150. A receiver operating characteristic curve was applied to evaluate the diagnostic value of miR‐150. The effect of miR‐150 on neuroinflammation was analyzed by examining its correlation with proinflammatory cytokines and gain‐of‐function experiments in microglia treated with LPS. Results: Serum miR‐150 expression was downregulated in PD patients compared with the healthy controls, and served as a candidate diagnostic biomarker for the screening of PD cases. Negative correlation was found between miR‐150 levels and the levels of procytokines in PD patients. By the treatment of LPS, microglia BV2 cells had a reduced expression of miR‐150, and the enhanced neuroinflammatory responses were inhibited by the overexpression of miR‐150. AKT3 was verified as a target of miR‐150 in BV2 cells. Conclusion: All the data of this study revealed that the decreased serum miR‐150 serves as a potential diagnostic biomarker. The methods to increase miR‐150 expression may have a beneficial effect in PD via suppressing the neuroinflammation by targeting AKT3. Abstract : The downregulated expression of miR‐150 serves as a diagnostic biomarker of Parkinson's disease.Serum miR‐150 levels are correlated with Parkinson's patients' inflammation and miR‐150 is decreased in microglia by LPS treatment. miR‐150 can inhibit neuroinflamation by targeting AKT3.